Novelties in the genus Polygonum (Polygonaceae) in Turkey - Keski̇n Mustafa; Severoğlu Zeki̇ (Phytotaxa, 2022)
This paper presents some novelties from the genus Polygonum (Polygonaceae) in Turkey. The study includes along with the description of a new species P. urnigera together with three new records from Istanbul; P. buxiforme, P. neglectum, and P. rurivagum. The distribution records of all these species have been included along with photographs and illustrations of the new species. The paper presents a new key for Polygonum s.str. (sect. Polygonum) species in Turkey.